Caffeic Acid Phenethyl Ester (CAPE) Improves Boar Sperm Quality and Antioxidant Capacity in Liquid Preservation (17°C) Linked to AMPK Activity Maintenance - Lan, Qun; Xue, Li'e; Cao, Jiacheng; Xie, Yingyu; Xiao, Tianfang; Fang, Shaoming (Frontiers in Veterinary Science, 2022)
Abstract Liquid preservation of boar sperm is crucial for artificial insemination application in the pig production. However, time-dependent oxidative damage to sperm is one of the major challenges during liquid preservation period. Caffeic acid phenethyl ester (CAPE) possesses excellent antioxidant properties which has a potential therapeutic use in reproductive organ injury linked to oxidative stress. AMPK involves in modulating the cellular redox state exerts beneficial effect on sperm preservation. In the present study, we firstly assessed different concentrations of CAPE affect sperm quality during liquid storage to determine the appropriate addition. To further investigate whether CAPE exerts protective effects on boar sperm through modulation of AMPK activity, sperm quality parameters, antioxidant capacity, and marker proteins expressions were evaluated under co-incubation with H2O2. The results showed that sperm treated by 210 μmol/L CAPE exhibited the highest motion parameters (total motility and progressive motility) and best functional integrity (mitochondrial activity, plasma membrane integrity and acrosomal integrity). Even in the presence of H2O2, addition of 210 μmol/L CAPE not only significantly improved sperm quality parameters, but also elevated CAT, SOD, and GSH-Px activities to enhance sperm antioxidant capacity. In addition, we found that CAPE could affect the protein activities of AMPK, phospho-AMPKα (p-AMPK), SOD, and Caspase-3 regardless of whether H2O2 presence or not. Our findings suggested that CAPE has potential application in liquid preservation of boar sperm and preliminary indicated that CAPE-induced improvement of sperm quality and antioxidant capacity should be mediated through conservation of AMPK activity. Further studies are required to illustrate the specific mechanism by which CAPE attenuates oxidative stress-mediated damages dependent on AMPK activity. Keywords: Boar sperm, liquid preservation, CAPE, AMPK, sperm quality, antioxidant capacity